Uji Organoleptik Dan Kandungan Vitamin C Pada Jus Jambu Mete (Anacardium occidentale L.) Dengan Pewarna Alami Daging Buah Naga (Hylocereus polyrhizus) Dan Penambahan Madu - Suseno, Agus; , Dra. Suparti, M.Si (2015)
The purpose of this study is to determine vitamin C content of cashew juice with natural dyes flesh dragon fruit and honey adding with quantity varying composition. Data collection techniques of the research is quantitative descriptive. The research used randomized complete design with three replicates of two factors. Levels tested of vitamin C uused titration method. Analysis of the test data used ANOVA TwoWay, wheares the organoleptic test and acceptance used qualitative descriptive analysis (questionnaire). The results shows there is an effect of adding flesh dragon fruit as a natural dyes on levels of vitamin c cashew juice and there is no effect of honey adding as a natural dyes on levels of vitamin C cashew juice. The conclusion shows that the highest levels of vitamin C cashew juice 61,455 mg on treatment of dragon fruit 125g additions and 18% honey additions. The lowest levels of vitamin c cashew juice 45,300 mg in the treatment without dragon fruit and honey adding. The results of organoleptic test cashew juice panelists preferred the addition of 75g treatment dragon fruit and 18% honey.